THE STUDY OF ENGLISH DEPARTMENT STUDENTS’ ERRORS IN USING GERUNDS - Partini Puji Rahayu; Mazrul Aziz; Zahrida . (Journal of English Education and Teaching, 2017)
This study aims to find out types of error in using gerunds, the most dominant error and the causes of error made by the students of the sixth semester of English Department FKIP UNIB 2016/2017 in using gerunds. The title of this paper is “The Study of English Department Students’ Errors in Using Gerunds (A Case Study at the Students of the Sixth Semester of English Department FKIP UNIB 2016/2017). In term of research methodology, the researcher used both quantitative and qualitative method in analyzing the data. The technique of collecting the data in this research was a composed test. The subject of this study was 79 students in the sixth semester of English Department FKIP UNIB 2016/2017. The result of this research showed that the students of the sixth semester of English Department FKIP UNIB 2016/2017 made errors in using eight types of gerunds. They were gerund as object of preposition, gerund as subject of a sentence, gerund as direct object of certain verbs, gerund as the complement of a sentence, gerund after special expressions, gerund as passive form, gerund as possessive and gerund used in the negative adjective ‘no’. The most dominant error made by the students of the sixth semester of English Department FKIP UNIB 2016/2017 in using gerunds was gerund as direct object of certain verbs. In this research, the researcher found three causes of error in using gerunds. They were overgeneralization, ignorance of rule instructions and incomplete application of rules. Ignorance of rule instructions became the dominant cause in this research. The errors made by the students in using eight types of gerunds were caused by ignorance of rule restriction because the students did not master the rule in grammar especially in learning gerunds